Tat[o]ueur : pouvoirs du tatouage dans Little Tulip, de Jerome Charyn et François Boucq - Sophie Vallas (Transatlantica)
Little Tulip (2014) is the third collaboration between US writer Jerome Charyn and French comic strip artist François Boucq. This graphic novel moves back and forth between the USSR of the 1940s and 1950s and New York City in the 1970s to tell the story of Paul, a US-born tattoo artist who spent his childhood in a Gulag colony in Siberia where, as Pavel, he learnt his craft. Drawing and tatooing are at the heart of the narrative, both Charyn and Boucq attempting to probe their powers: when Pavel/Paul becomes an artist in the Gulag, he learns to adorn captive bodies with insignia that reflect the strict hierarchy of the camp or with codified symbols that tell the stories of the criminals’ lives, but he also learns to penetrate those savage men’s personalities and thus to save his own skin by beautifully inking the skins of others. Beyond exposing the very concrete powers that enable the young tatoo artist to survive in Siberia by both respecting and transgressing the rules of the camp, and then to roam the violent streets of New York city, Little Tulip explores the laws of art that each drawing contains: rules that allow the artist to walk the thin line between art and magic, where the indelible ink of tatoo can paradoxically give birth to invisibility.